(untitled) (Research, Society and Development, 2021)
Açaí (Euterpe precatoria Mart.) is a plant widely cultivated in the northern region of Brazil. Its fruits have been gaining worldwide prominence due to their countless benefits for human health. Consequently, pulp production has increased considerably in recent years, generating significant amounts of waste (mainly seeds). As these residues do not have proper disposal, they are either discarded in the environment or incinerated, causing numerous environmental impacts. To present alternative applications of these residues, this study aimed to evaluate the lignocellulosic contents of açaí seeds – extracts, ash, lignin, cellulose (α-cellulose and hemicellulose) – in addition to extracting and characterizing the cellulose obtained from this abundant residue. The seeds and the extracted cellulose were characterized by several techniques: X-ray fluorescence (XRF), X-ray diffraction (XRD), Attenuated total reflectance with Fourier transform infrared spectroscopy (ATR/FTIR), and thermogravimetry (TGA). In this study, the high potential of using açaí seeds as an alternative source of cellulose was confirmed, since presents 45.5% of this polymer and all the characterization techniques show the purity of the extracted cellulose (type I).